Tourism in the Republic of Kazakhstan: development problems and prospects - Zhomartova, G.Zh. (Изд-во КарГУ, 2013)
This article describes the research of current state and analysis of prospects for the tourism development in the Republic of Kazakhstan, including the following objectives solved: the basic theoretical aspects of tour- ism are studied; the value of tourist activity in the economy of the Republic of Kazakhstan is revealed; the structure of the tourism industry is studied and the potential of the tourism resources of the country is analyzed; the analysis of the factors influencing on the development of tourism in the country is carried out, the main directions and prospects of tourism development in the Republic of Kazakhstan are revealed. The study was performed on the basis of data from the Agency of Statistics of the Republic of Kazakhstan.
Keywords: Kazakhstan; tourism; types of tourism; tourism development; tourism industry; products of tourism; EXPO-2017